Examination of Oribatid Mites for Cysticercoids of Moniezia Sp - K. K, Reena; Thomas, Jobin; Chacko, Nirmal; Sabu, Lucy; Devada, K (International Journal of Veterinary Sciences Research, 2015)
Two hundred oribatid mites separated from the soil collected from the vicinity of the manure pits of Cattle and Goat farms under the Kerala Veterinary & Animal Sciences University, Mannuthy using Berlese apparatus. All the mites separated were identified upto family level as Mochlozetidae. On dissection of all the collected mites, one fully developed and an immature cysticercoid could be detected from only one mite.